Biomass gel electrolyte with high interfacial compatibility as well as preparation method and application of biomass gel electrolyte
This invention addresses the problems existing in the preparation methods of biomass gel electrolytes, providing a method for preparing a biomass gel electrolyte with high interfacial compatibility. This method overcomes the shortcomings of existing gel electrolytes in suppressing zinc dendrite growth and side reactions, thereby improving the cycle stability and safety of zinc-ion batteries.
Patent Information
- Application Number
- CN202510949250.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-11-28
AI Technical Summary
Existing gel electrolytes are not very effective in suppressing zinc dendrite growth and side reactions, which affects the cycle stability and safety of zinc-ion batteries.
A method for preparing biomass gel electrolyte with high interfacial compatibility is adopted, which includes taking a metal salt solution, acrylamide, a biomass polymer containing hydrophilic groups, crosslinking agent, crosslinking agent, and crosslinking agent and stirring evenly to obtain a precursor liquid, carrying out a polymerization reaction, and allowing it to stand and cool to obtain biomass gel electrolyte with high interfacial compatibility.
The prepared biomass gel electrolyte has high interfacial compatibility, good mechanical properties and high ionic conductivity. It inhibits zinc dendrite growth, improves the long-cycle performance of zinc-ion batteries, and is simple to operate and has low cost.
Smart Images

Figure CN121035384A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of energy materials, and particularly relates to a biomass gel electrolyte with high interfacial compatibility and a preparation method and application thereof. BACKGROUND
[0002] Aqueous zinc-ion batteries have attracted extensive attention due to their high safety, low redox potential (-0.76 V vs. standard hydrogen electrode), high theoretical capacity (5854 mA h cm -3 ), and low cost. However, the cycle stability of zinc-ion batteries is closely related to the metal zinc anode, mainly because the zinc anode produces severe dendrites in aqueous solution during the cycling process, accompanied by side reactions such as hydrogen evolution and corrosion, which inevitably leads to poor reversibility and even short-circuit failure of zinc-ion batteries, further hindering the commercial development of aqueous zinc-ion batteries. Optimizing the electrolyte composition has been proven to be an effective strategy to solve these problems, such as electrolyte additives, water-in-salt electrolytes, eutectic electrolytes, and hydrogel electrolytes. Among them, hydrogel electrolytes are the most attractive. Because they can not only effectively regulate the interfacial ion transport, adjust the Zn deposition / stripping process, and limit the growth of dendrites, but also avoid the leakage of electrolyte, thereby improving the safety.
[0003] Gel electrolytes can effectively bind water molecules due to their cross-linked polymer chain network structure, reduce the activity of free water, and thus significantly inhibit the side reactions such as hydrogen evolution and corrosion on the surface of the zinc anode. In particular, the coordination between Zn 2+ and the functional groups on the polymer chain in the hydrogel electrolyte can establish a more ordered ion transport channel. This unique ion transport mechanism not only enables uniform deposition of Zn 2+ , but also effectively regulates the electrochemical process at the electrode / electrolyte interface. Compared with traditional liquid electrolytes, hydrogel electrolytes show significant advantages in inhibiting zinc dendrite growth and side reactions. For example, the cross-linked hydrogel of single-network polyacrylamide (PAM) can block active H2O, coordinate with Zn 2+ ions through the negatively charged carbonyl groups in the molecular chain, and improve the distribution of Zn 2+ ions, thereby limiting the dendrite growth of the Zn anode.
[0004] However, most of the currently reported gel electrolytes only consider the effect of a single factor on the growth of dendrites and the inhibition of side reactions, and the treatment effect is not obvious. Therefore, it is of great significance for the development of aqueous zinc-ion batteries to develop a new type of high-performance gel electrolyte with a multi-layer cross-linked network structure, high ionic conductivity, good mechanical properties, and the ability to combine multiple strategies for inhibiting zinc dendrites. SUMMARY
[0005] This section is intended to introduce some aspects of one or more embodiments of the present application, which are described below. This section is not intended to limit the scope or content of the application in any way. The concepts described herein can apply equally to any embodiment of the application.
[0006] In view of the above and / or existing problems in the prior art, the present application is proposed.
[0007] Therefore, the purpose of the present application is to overcome the deficiencies in the prior art, and to provide a preparation method of a high interfacial compatibility biomass gel electrolyte.
[0008] To solve the above technical problems, the present application provides the following technical solutions:
[0009] After the metal salt solution, acrylamide and biomass polymer containing hydrophilic groups are stirred uniformly, a crosslinking agent and an initiator are added and stirred uniformly to obtain a precursor solution;
[0010] The precursor solution is subjected to a polymerization reaction, and is cooled to obtain a high interfacial compatibility biomass gel electrolyte;
[0011] The biomass polymer includes one or more of gum arabic, hydroxyethyl cellulose, soluble starch, gelatin, konjac gum, chitosan, xanthan gum and guar gum.
[0012] As a preferred solution of the preparation method of the high interfacial compatibility biomass gel electrolyte, the metal salt includes one or more of zinc salt and manganese salt; the crosslinking agent includes one or more of N,N-methylene bisacrylamide, polyethylene glycol diacrylate and dicumyl peroxide; and the initiator includes one or more of potassium persulfate, ammonium persulfate and dibenzoyl peroxide.
[0013] As a preferred solution of the preparation method of the high interfacial compatibility biomass gel electrolyte, the zinc salt includes one or more of zinc trifluoromethane sulfonate, zinc sulfate, zinc chloride and zinc acetate; and the manganese salt includes one or more of manganese sulfate and manganese chloride.
[0014] As a preferred solution of the preparation method of the high interfacial compatibility biomass gel electrolyte, the concentration of the metal salt solution is 0.1-5 mol / L.
[0015] As a preferred solution of the preparation method of the high interfacial compatibility biomass gel electrolyte, the mass ratio of the acrylamide to the biomass polymer containing hydrophilic groups is 1:0.01-0.5.
[0016] In a preferred embodiment of the preparation method of the biomass gel electrolyte with high interfacial compatibility according to the present invention, the amount of acrylamide used relative to the precursor solution is 4.9-7.5 wt%; and the amount of the biomass polymer containing hydrophilic groups used relative to the precursor solution is 0.01-10 wt%.
[0017] In a preferred embodiment of the preparation method of the biomass gel electrolyte with high interfacial compatibility according to the present invention, the crosslinking agent is used in an amount of 0.001 to 10 wt% relative to the precursor solution; and the initiator is used in an amount of 0.001 to 10 wt% relative to the precursor solution.
[0018] In a preferred embodiment of the preparation method of the biomass gel electrolyte with high interfacial compatibility according to the present invention, the precursor solution undergoes a polymerization reaction, wherein the polymerization reaction temperature is 50-70°C and the time is 1-10h.
[0019] Another objective of this invention is to overcome the shortcomings of the prior art and provide a method for preparing a biomass gel electrolyte with high interfacial compatibility.
[0020] Another objective of this invention is to overcome the shortcomings of the prior art and provide an application of a biomass gel electrolyte with high interfacial compatibility in the preparation of aqueous zinc-ion batteries.
[0021] Beneficial effects of this invention:
[0022] (1) The biomass gel electrolyte prepared by the present invention not only has high interfacial compatibility, but also has the advantages of high ionic conductivity and good mechanical properties; among them, the natural biomass polymer rich in hydrophilic groups can interact with amide groups and water to form a large number of hydrogen bonds, giving the system excellent mechanical resilience, making it difficult for zinc dendrites to puncture the electrolyte membrane and cause short circuits.
[0023] (2) By reducing the content of free water through the abundant polar groups in the gel electrolyte, the growth of zinc dendrites and the occurrence of side reactions are suppressed, which significantly improves the long cycle performance of aqueous zinc-ion batteries.
[0024] (3) In addition, the present invention prepares gel electrolytes by thermally initiated free radical polymerization, which is simple to operate, easy to prepare, and low in cost. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 Comparison chart of the electrolyte prepared for the present embodiment 1 and comparative example 1 in the same conditions for plating / stripping in Zn / / Zn symmetric battery.
[0027] Figure 2 Comparison chart of the Tafel curve of the electrolyte prepared for the present embodiment 1 and comparative example 1 under the same conditions.
[0028] Figure 3 Comparison chart of the energy dissipation and fatigue resistance of the gel after continuous loading-unloading under 50% compressive strain for the electrolyte prepared for the present embodiment 1 and comparative example 1.
[0029] Figure 4 Comparison chart of the ionic conductivity of the electrolyte prepared for the present embodiment 1 and comparative example 1 measured by AC impedance method. DETAILED DESCRIPTION
[0030] In order to make the above objectives, features and advantages of the present application more apparent and comprehensible, the specific embodiments of the present application will be described in detail below with reference to the description and embodiments.
[0031] In the following description, a lot of specific details are set forth in order to provide a thorough understanding of the present application, but the present application can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without departing from the spirit of the present application, so the present application is not limited to the specific embodiments disclosed below.
[0032] Secondly, the "one embodiment" or "embodiment" referred to herein means that the specific features, structures or characteristics can be included in at least one implementation of the present application. "In one embodiment" appearing in different places in the specification does not mean the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments.
[0033] Embodiment 1
[0034] The present embodiment provides a preparation method of a biomass gel electrolyte with high interfacial compatibility, specifically:
[0035] (1) Dissolve Zn(OTF)2 in deionized water, stir uniformly at a speed of 500 rmp, and then constant volume to obtain a Zn(OTF)2 salt solution with a concentration of 2 mol·L -1 ;
[0036] (2) Take 10 mL of Zn(OTF)2 salt solution, 1.0 g of acrylamide, 0.1 g of gum arabic, stir for 3 h, then add 0.005 g of N,N-methylene bisacrylamide, 0.01 g of potassium persulfate, and stir until uniform, to obtain a precursor solution; wherein the amount of acrylamide used in the precursor solution is 6.09 wt%.
[0037] (3) After the precursor solution is polymerized at 60°C for 3 h, it is allowed to cool to obtain a polyacrylamide-gum arabic double-crosslinked hydrogel electrolyte, i.e., a biomass gel electrolyte with high interfacial compatibility.
[0038] Comparative Example 1
[0039] This comparative example provides a method for preparing an electrolyte, which differs from Example 1 in that gum arabic is not added, and the rest of the preparation process is the same as that of Example 1, and the electrolyte of this comparative example is prepared.
[0040] The biomass gel electrolyte prepared in Example 1 and the polyacrylamide gel electrolyte prepared in Comparative Example 1 were subjected to plating / delamination in a Zn / / Zn symmetric battery under the same conditions, and the results are shown in Figure 1 .
[0041] As can be seen from Figure 1 , the polyacrylamide electrolyte exhibited a significant short-circuit phenomenon after less than 800 h of cycling, while the gel electrolyte remained stable after 5000 h of charge-discharge cycling at a current density of 1 mA cm -2 , without exhibiting a significant short-circuit phenomenon, indicating that the gel electrolyte has good interfacial stability with the anode, and demonstrating that the synergistic interaction between acrylamide and gum arabic plays a key role in improving the cycling stability of the zinc anode.
[0042] The biomass gel electrolyte prepared in Example 1 and the polyacrylamide gel electrolyte prepared in Comparative Example 1 were tested for Tafel curves under the same conditions, and the results are shown in Figure 2 .
[0043] As can be seen from Figure 2 , under the same conditions, the prepared gel electrolyte has a smaller corrosion current and a larger corrosion voltage than the polyacrylamide electrolyte, and can better inhibit the corrosion of the zinc negative electrode.
[0044] The biomass gel electrolyte prepared in Example 1 and the polyacrylamide gel electrolyte prepared in Comparative Example 1 were subjected to continuous loading-unloading experiments under a compression strain of 50%, and the energy dissipation and fatigue resistance of the hydrogel were evaluated, and the results are shown in Figure 3 .
[0045] As can be seen from Figure 3As can be seen from the continuous compression stress-strain curve, no obvious deviation is observed from 2 to 10 cycles. Even after 10 times of rapid compression test, the recovery efficiency of the hydrogel remains at 98%, which is far superior to the mechanical rebound performance of polyacrylamide electrolyte, making it difficult for zinc dendrite by-products to pierce the electrolyte membrane and cause short circuit of the battery.
[0046] The ionic conductivity of the biomass gel electrolyte prepared in Example 1 and the polyacrylamide gel electrolyte prepared in Comparative Example 1 was measured by AC impedance method, and the results are shown in Table 1. Figure 4 and Table 1.
[0047] Table 1 Electrochemical performance of biomass gel electrolyte and polyacrylamide gel electrolyte
[0048]
[0049] According to Table 1 and Figure 1 , the ionic conductivity of the biomass gel electrolyte is 28.3 mS cm -1 , which is superior to the ionic conductivity of most reported gel electrolytes, indicating that the gel electrolyte can improve the electrochemical performance of zinc ion battery.
[0050] Example 2
[0051] This embodiment provides a preparation method of a biomass gel electrolyte with high interfacial compatibility. The difference from Example 1 is that the gum arabic in step (2) is replaced by guar gum, konjac gum, xanthan gum, chitosan, soluble starch, and hydroxyethyl cellulose gum, respectively. The rest of the preparation process is the same as that of Example 1, and the gel electrolyte of this embodiment is prepared.
[0052] The electrochemical performance of the electrolyte prepared by different biomass polymers in Example 2 was tested, and the results are shown in Table 2.
[0053] Table 2 Influence of biomass on electrochemical performance of gel electrolyte
[0054]
[0055]
[0056] As can be seen from Table 1, the type of biomass macromolecule has a significant effect on the electrochemical performance. Among them, the gel electrolyte prepared from gum arabic has the highest ionic conductivity, and the symmetric battery has a current density of 1 mA cm -2The current density under the longest cycle time, the best effect. This is due to the different functional groups contained in biological macromolecules, the complex ability of zinc ions, the interaction mode is different, moderate complexation can guide the migration direction of zinc ions, but if the complexation is too strong, it will be difficult to remove the complexation of zinc ions, thereby affecting the ion conduction rate. Gum arabic has a multi-hydroxyl structure, which complexes with zinc ions to guide the directional transport of zinc ions, improving the migration kinetics of zinc ions. At the same time, gum arabic has adhesion properties, which can improve the interface interaction with the zinc negative electrode, thereby improving the transport and deposition of zinc ions.
[0057] Example 3
[0058] The present embodiment provides a preparation method of a biomass gel electrolyte with high interfacial compatibility. The difference between the present embodiment and Example 1 is that the amount of gum arabic in step (2) is adjusted to 0.05g, 0.2g, 0.3g, and 0.4g, respectively, i.e. the mass ratio of acrylamide to gum arabic is 1:0.05, 1:0.2, 1:0.3, and 1:0.4. The rest of the preparation process is the same as that of Example 1, and the gel electrolyte of the present embodiment is prepared.
[0059] The electrochemical performance of the gel electrolyte prepared by different amounts of gum arabic in Example 3 was tested, and the results are shown in Table 3.
[0060] Table 3 Effect of biomass amount on the electrochemical performance of gel electrolyte
[0061]
[0062] From the data in Table 3, it can be seen that as the amount of gum arabic increases, the conductivity of the electrolyte decreases slightly, and the symmetric battery has a discharge capacity of 600mAh g -2 The cycle time under current density is shortened. Gum arabic is used in gel electrolyte to construct ion transport channels, and appropriate amount of gum arabic can form a suitable pore structure to enable ions to freely transport in the gel electrolyte. However, excessive addition of gum arabic may significantly increase the viscosity of the gel electrolyte, resulting in poor solution flowability and reduced mixing uniformity. During polymerization, excessive gum arabic may form too many crosslinking points, making the network structure of the gel electrolyte too tight, thereby limiting the ion transport channels and increasing the resistance of ion migration, ultimately leading to a decrease in the ion conductivity of the battery and poor performance.
[0063] Example 4
[0064] The present embodiment provides a preparation method of a biomass gel electrolyte with high interfacial compatibility. The difference between the present embodiment and Example 1 is that the temperature of the polymerization reaction in step (3) is adjusted to 50°C and 70°C, respectively. The rest of the preparation process is the same as that of Example 1, and the gel electrolyte of the present embodiment is prepared.
[0065] The effect of the polymerization temperature on the electrochemical performance of the gel electrolyte in Example 4 was tested, and the results are shown in Table 4.
[0066] Table 4 Effect of the polymerization temperature on the electrochemical performance of the gel electrolyte
[0067]
[0068] As can be seen from Table 4, the temperature of the polymerization reaction has a slight effect on the electrochemical performance of the electrolyte, and the gel electrolyte prepared by polymerization at 60°C has the best performance.
[0069] Example 5
[0070] This example provides a method for preparing a biomass gel electrolyte with high interfacial compatibility. The difference from Example 1 is that the amount of acrylamide in step (2) is adjusted to 0.8 g and 1.2 g, i.e., the amount of acrylamide is 4.87 wt% and 7.31 wt% compared to the precursor solution, and the rest of the preparation process is the same as in Example 1, and the gel electrolyte of this example is prepared.
[0071] The effect of the amount of acrylamide on the electrochemical performance of the gel electrolyte in Example 5 was tested, and the results are shown in Table 5.
[0072] Table 5 Effect of the amount of acrylamide on the electrochemical performance of the gel electrolyte
[0073]
[0074]
[0075] As can be seen from Table 5, the amount of acrylamide differs by about 1 wt%, and the cycle time of the symmetrical battery prepared from the gel electrolyte at a current density of 1 mA cm -2 The amount of acrylamide in the gel electrolyte is used to construct ion transport channels. An appropriate amount of acrylamide can form a suitable pore structure, allowing ions to be freely transported in the gel electrolyte. Too much acrylamide can form too many crosslinking points during polymerization, making the network structure of the gel electrolyte too tight, thereby limiting the ion transport channels and increasing the resistance of ion migration, ultimately leading to a decrease in the ionic conductivity of the battery and poor performance. Too little acrylamide can result in an unstable network structure of the gel, poor mechanical properties, and a non-uniform and developed pore structure that cannot efficiently transport zinc ions.
[0076] In conclusion, the present application provides a biomass gel electrolyte with high interfacial compatibility and a preparation method thereof. It is found that, by combining specific biomass macromolecular species with optimized preparation process, a gel electrolyte with high interfacial compatibility, high ionic conductivity and good mechanical properties can be finally prepared. The natural biomass macromolecule rich in hydrophilic groups can interact with amide groups and water to form a large number of hydrogen bonds, giving the system excellent mechanical resilience performance, so that the zinc dendrite is not easy to pierce the electrolyte film to cause short circuit.
[0077] In addition, the rich polar groups in the gel electrolyte reduce the content of free water, thereby inhibiting the growth of zinc dendrites and the occurrence of side reactions, and significantly improving the long cycle performance of the aqueous zinc ion battery. The gel electrolyte prepared by the thermal radical polymerization method is simple to operate, easy to prepare and low in cost.
[0078] It should be noted that the above examples are only used to illustrate the technical solutions of the present application and are not limiting. Although the present application has been described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present application can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application, which should be covered by the scope of the claims of the present application.
Claims
1. A method for preparing a biomass gel electrolyte with high interfacial compatibility, characterized in that: include, After mixing a metal salt solution, acrylamide, and a biomass polymer containing hydrophilic groups evenly, a crosslinking agent and an initiator are added and mixed evenly to obtain a precursor solution. The precursor solution was subjected to a polymerization reaction, and then allowed to stand and cool to obtain a biomass gel electrolyte with high interfacial compatibility. The biomass polymers include one or more of gum arabic, hydroxyethyl cellulose, soluble starch, gelatin, konjac gum, chitosan, xanthan gum, and guar gum.
2. The method for preparing a highly interfacially compatible biomass gel electrolyte as described in claim 1, characterized in that: The metal salt includes one or more of zinc salt and manganese salt; the crosslinking agent includes one or more of N,N-methylenebisacrylamide, polyethylene glycol diacrylate, and dicumyl peroxide; the initiator includes one or more of potassium persulfate, ammonium persulfate, and benzoyl peroxide.
3. The method for preparing a biomass gel electrolyte with high interfacial compatibility as described in claim 2, characterized in that: The zinc salt includes one or more of zinc trifluoromethanesulfonate, zinc sulfate, zinc chloride, and zinc acetate; the manganese salt includes one or more of manganese sulfate and manganese chloride.
4. The method for preparing a biomass gel electrolyte with high interfacial compatibility as described in claim 1, characterized in that: The concentration of the metal salt solution is 0.1–5 mol / L.
5. The method for preparing a biomass gel electrolyte with high interfacial compatibility as described in claim 1, characterized in that: The mass ratio of acrylamide to the biomass polymer containing hydrophilic groups is 1:0.01 to 0.
5.
6. The method for preparing a highly interfacially compatible biomass gel electrolyte as described in claim 1, characterized in that: The amount of acrylamide used relative to the precursor solution is 4.9–7.5 wt%; the amount of the biomass polymer containing hydrophilic groups used relative to the precursor solution is 0.01–10 wt%.
7. The method for preparing a highly interfacially compatible biomass gel electrolyte as described in claim 1, characterized in that: The crosslinking agent is used in an amount of 0.001–10 wt% relative to the precursor solution; the initiator is used in an amount of 0.001–10 wt% relative to the precursor solution.
8. The method for preparing a biomass gel electrolyte with high interfacial compatibility as described in claim 1, characterized in that: The precursor liquid undergoes a polymerization reaction, wherein the polymerization reaction temperature is 50–70°C and the time is 1–10 h.
9. The biomass gel electrolyte with high interfacial compatibility prepared by the preparation method according to any one of claims 1 to 8.
10. The application of the highly interfacially compatible biomass gel electrolyte as described in claim 9 in the preparation of aqueous zinc-ion batteries.